The Influence of E-Service Quality, Satisfaction, and Electronic Word-of-Mouth on the Repeat Usage of Private Transportation Services in Upper Northern Region of Thailand - Lertpongsin, Kaschanan; Srisook, Phoom; Sopakul, Rapeepan (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2026)
The objectives of this research were: 1) to study the significance of electronic service quality, satisfaction, electronic word-of-mouth, and repurchase intention among users of private transportation services; and 2) to examine the influence of electronic service quality, satisfaction, and electronic word-of-mouth on repurchase intention among users of private transportation businesses in the upper northern region of Thailand. The population consisted of users of private transportation businesses in the upper northern region of Thailand across nine provinces: Chiang Rai, Nan, Phayao, Chiang Mai, Mae Hong Son, Phrae, Lampang, Lamphun, and Uttaradit, who had used the services at least once within the previous six months. This study employed a quantitative research approach. The sample group comprised 400 respondents selected through purposive sampling. The research instrument used for data collection was a questionnaire. Data were analyzed using descriptive statistics, including frequency, percentage, and standard deviation, while inferential statistics were analyzed using Structural Equation Modeling (SEM). The findings revealed that all factors were rated at a high level of importance. The model demonstrated a good fit with the empirical data, with the following indices: X²/df = .919, GFI = .941, AGFI = .926, CFI = 1.000, NFI = .938, and RMSEA = .000. Furthermore, quality of electronic service has had a positive influence on satisfaction. Electronic service quality also positively influenced electronic word-of-mouth. However, electronic service quality had a negative influence on repurchase intention. Satisfaction positively influenced repurchase intention. In addition, electronic word-of-mouth positively influenced repurchase intention with the significance level. This study can serve as a guideline for private transportation business operators to continuously improve the quality of electronic services in order to create positive experiences for customers and increase the likelihood of repeat service usage.